Sistem Monitoring Aktifitas Laboratorium Berbasis Web - Nazir, M; Nasir, Muhammad; Indrawati, Indrawati (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2022)
Monitoring is the activities used to create conditions, including certain behaviors or activities with the aim that all data entered or information needed from the observations. Monitoring is generally done using a single board computer. Then it can be controlled and controlled with only a central controller. The purpose of this study is to monitor in the laboratory so that it can run optimally and optimally. The system is designed to monitor the room, temperature and heating functions, lights, AC (AC) and other electrical equipment designed using terminals on raspbian operating systems, python and php, as a reason to make the user interface. Testing is done by doing measurements and observations in the laboratory. The results of this study state that the temperature sensor test with temperature difference with the normal temperature meter results that shows that the heating lamp device, and the air conditioning machine (AC) is successfully carried out in real time.Keywords: Laboratory Room Monitoring. Temperature setting, Raspberry Pi